In Vitro Seed Germination and Seedling Development of a Rare Indonesian Native Orchid Phalaenopsis amboinensis J.J.Sm. (3rd February 2019) - Utami, Edy Setiti Wida; Hariyanto, Sucipto
Abstract : Phalaenopsis amboinensis, an epiphytic orchid, has a great potential for commercial exploitation in the cut-flower industry. It is difficult to propagate vegetatively as it naturally grows slowly. Therefore, there is a need to improve the propagation methods to avoid endangering its natural populations. The objective of this study was to identify the best medium and organic supplements for seed germination and plantlets development of P. amboinensis . Seeds from 4-month-old hand-pollinated orchids were sown on different strengths of MS and VW culture media: Murashige and Skoog (MS), 1/2 MS, Vacin and Went (VW), and 1/2 VW. Optimum seed germination, i.e., 90.7%, was achieved on VW medium. VW medium was suitable for seedling formation and allowed 51.4% of seedling development from protocorm within 10 weeks of culture. When 15% (v/v) coconut water was added together with banana homogenate (10 g·L −1 ) to the VW medium, the plantlets grew to the highest length and had the highest dry weight (62.1 mm and 15.5 g, respectively). The roots and leaves of the plantlets grew vigorously in this medium. Plants regenerated via in vitro seed germination processes were successfully acclimatized in greenhouse conditions, and the survival rate was more than 85%.